ANALYSIS OF MOTOR ELEMENTS IN ACADEMICS OF THE COURSE OF PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
Besides valuing the importance of the motor capacities for any individual as a health predictor in the accomplishment of physical activities and exercises, one can also notice its importance for the accomplishment of professional activities. The present study has aimed at identifying and correlating levels of large and fine coordination, equilibrium, proprioception, and time of simple reaction and of choice in academics of the course of Physical Education. Thirty five academics of the course of full degree in Physical Education with the same studied disciplines took part in the study. The instruments applied were the Burpee's test (Johnson & Nelson, 1979) in order to verify the large motor coordination; the test of fine motor coordination - Manual Abilities (Andreotti e  Okuma, 1999); the test of Equilibrium - Parada da Cegonha - Stork Stan  (Johnson & Nelson, 1979); the Test of  Self-Perception (Paixão, 1981), and the Test of Reaction Time by using a software. The Pearson's correlation has been applied to verify the relation between the variables with significance level of 0, 05 through the SPSS statistic package version 11.0. The results have shown the existence of a statistically significant correlation (0,365) only between the results of time of simple reaction and time of choice reaction.